Evaluation of ajowain (Trachyspermum ammi L.) genotypes suitable for semi arid re- gions. - S P Choudhary, Dhirendra Singh, (Journal of Spices and Aromatic Crops, 2008)
Forty two genotypes of ajowain collected from various sources were planted in RandomizedBlock Design in three replications at Research Farm, S.K.N. College of Agriculture, Jobner toassess the degree of genetic variability, heritability and genetic advance for seed yield perplant in ajowain (Trachyspermum ammi Linn.). The analysis of variance revealed significantdifferences among the genotypes for all the characters studied viz., day to 50% flowering,plant height, branches per plant, umbels per plant, umbellets per umbel, seeds per umbel,1000-seed weight, harvest index and seed yield per plant. The estimates of heritability (broadsense) were high for plant height, umbels per plant, harvest index and seed yield per plantwhereas, it was moderate for days to 50% flowering, branches per plant, umbellets per umbel,seeds per umbel and 1000-seed weight. The genotypic coefficient of variation and geneticadvance expressed as percentage of mean were high for harvest index and seed yield perplant and moderate to low for umbels per plant, seeds per umbel, branches per plant, plantheight, days to 50% flowering, umbellets per umbel and 1000-seed weight, respectively.